Dynamic Threshold Based Load Balancing and Server Consolidation in Cloud - Megharaj, Geetha; Kabadi, Mohan G (International Journal of Computer Sciences and Engineering, 2025)
High power consumption in Cloud Data center leads to high emissions of carbon which is unsuitable for environment. Energy consumption in the data center can be reduced by balancing load among active physical nodes and minimizing the number of active servers which are lightly loaded. Static lower and upper thresholds are not suitable for dynamically changing resource usage of physical machines. Dynamic Threshold based load balancing algorithms are proposed: i)Upper threshold dynamically varied based on CPU utilization and the Lower Threshold is predefined. ii) The average utilization of all the machines in the datacenter is used to define Upper Threshold. System is monitored at regular intervals and whenever server load goes above the Upper Threshold or lower than Lower Threshold, system identified as in imbalance state and Virtual Machine migration is initiated for load balance and for server consolidation. Simulation results shows the proposed schemes can improve resource utilization and energy.